The Marianas web [videorecording (DVD)] - Soriquez, Ruben Maria; Soriquez, Ruben Maria; Cavaletto, Andrea; Calvise, Marco; Galeotti, Asia; Ocampo, Alexa (Leomark Studios, 2026)
In a remote, lonely town, a a farmer becomes enthralled by an online romance, only to discover the dark, sinister side of his digital obsession. The Mariana's Web is a chilling sci fi horror that explores isolation, technology, and the dangers lurking beneath virtual connections.